Rehearsing for an audience: students learning science through video production. (1st April 2011) - Hilton, Geoff
A study adapting the writing-to-learn in science model to include video production was conducted. Two Year 7 classes ( N = 21, N = 22) in mixed ability and gender groups completed a science investigation. One class recorded their findings using a written text (posters) and the other produced videos. Quantitative results revealed greater learning gains for the video producers. Video data analysis indicated heightened awareness of audience for video producers and a subsequent tendency to rehearse before filming; both contributed to learning gains. Educational technological innovations such as in-class video production, combined with appropriate teacher pedagogy, can enhance students' science learning.